2023
DOI: 10.1021/acsestwater.2c00255
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Fecal Contamination in an Urbanized Tropical Lake and Incidence of Acute Diarrheal Disease

Abstract: Aquatic ecosystems of tropical countries are vulnerable to fecal contamination that could cause spikes in the incidences of acute diarrheal disease (ADD) and challenge public health management systems. Vembanad lake, situated along the southwest coast of India, was monitored for one year (2018−2019). Escherichia coli, an indicator of fecal contamination, was prevalent in the lake throughout the year. Multiple antibiotic resistance among more than 50% of the E. coli isolates adds urgency to the need to control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…While there are limitations in the applicability of multi-spectral visible radiometry under cloudy conditions, the use of Sentinel-2 and other MSI sensors can increase the temporal coverage of flood maps considerably, even if only partial maps are available. Additional benefits lie in the application of multi-spectral observations for water quality monitoring [10][11][12]55]. Recent work has indicated that heavy rains and floods are tied to the dynamics of microbial pollutants in the water, including pathogenic bacteria such as Vibrio cholerae and Escherichia coli [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there are limitations in the applicability of multi-spectral visible radiometry under cloudy conditions, the use of Sentinel-2 and other MSI sensors can increase the temporal coverage of flood maps considerably, even if only partial maps are available. Additional benefits lie in the application of multi-spectral observations for water quality monitoring [10][11][12]55]. Recent work has indicated that heavy rains and floods are tied to the dynamics of microbial pollutants in the water, including pathogenic bacteria such as Vibrio cholerae and Escherichia coli [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Additional benefits lie in the application of multi-spectral observations for water quality monitoring [10][11][12]55]. Recent work has indicated that heavy rains and floods are tied to the dynamics of microbial pollutants in the water, including pathogenic bacteria such as Vibrio cholerae and Escherichia coli [11,12]. Therefore, it becomes important that mitigation measures include steps to prevent outbreaks of waterborne diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation